NIE LUBIĘ NIEMCÓW, BO NIE – O AUTOREFLEKSJI W POSTRZEGANIU INNYCH - Mihułka, Krystyna (Neofilolog, 2019)
The aim of this article is to present and discuss the results of a questionnaire carried out among secondary school students of German with a view to examining the students’ perception and assessment of the Germans. Analysis of the data provides an answer to the question whether secondary school students of German are able to think critically while assessing others or maybe, on the contrary, are only able to repeat others’ judgements without reflection. The discussion of the results of the questionnaire seems to indicate that, unfortunately, the majority of the secondary school students of German can hardly be regarded as reflective. In the second part of the article, the author puts forward some proposals which may prove important in the process of educating reflective foreign language teachers, and consequently, reflective students.